Willingness to pay for environmentally friendly products among low-income households along Coastal Peninsular Malaysia - Al Mamun, Abdullah; Fazal, Syed Ali; Ahmad, Ghazali; Yaacob, Mohd Rafi; Mohamad, Mohd Rosli (2018)
In an attempt to promote the mass consumption of environmentally friendly products in Malaysia, this study presents an investigation of the effects of several selected factors upon willingness to pay and purchase behavior of environmental-friendly products. This study employed a cross-sectional design, in which quantitative data were gathered from a total of 380 low-income household heads from 38 coastal districts in Peninsular Malaysia. The outcomes of this study revealed the positively significant effects of eco-literacy and environmental concern upon attitudes towards environmental-friendly products; normative beliefs and perceived behavioral control on willingness to pay for environmental-friendly products; as well as willingness to pay for environmental-friendly products and perceived behavioral control on payment behavior for environmental-friendly products, among low-income households in coastal Peninsular Malaysia. Programs and policies should therefore focus on promoting environmental awareness and knowledge concerning the relative advantages that are expected to improve willingness among consumers to pay for environmentally friendly products.